Trends in substance use and associated risk factors among adolescents in Belize - Oladeji, Olusola; Ma, Qihui; Vellos, Esner; Lai, Joanna; Shen, Annie; Legins, Ken; B. Pant, Sagun; Spyridou, Antria; Oladeji, Anjola; Longsworth, Errol; Augustine, Jeffan; Teyul, Jamid; et al. (International Journal Of Community Medicine And Public Health, 2025)
Background: Adolescents are at a crucial stage of development, making them more likely to engage in risk-taking behaviors, including substance use. This study aimed to describe the trends and patterns of substance use and risk factors among adolescents who accessed treatment and rehabilitation outreach services between 2017 and 2024. Methods: This exploratory study utilized both qualitative and quantitative methods. Results: During the reporting period, adolescents aged 10-19 years represented 45% (1,055 out of 2,365) of reported substance use cases. Marijuana and alcohol were the most frequently used substances among both genders, while cocaine and tobacco use were significantly lower, particularly among girls. The highest usage rates were observed among adolescents aged 15-19, with a notable gender disparity: 82% of reported cases were males, compared to 18% females. The risk factors were categorized using a socio-ecological approach into four themes: (1) individual factors: emotional stress; (2) interpersonal factors: household environment and peer pressure; (3) community factors: accessibility, affordability, lack of structured activities and recreational alternatives, and the influence of social media; and (4) policy factors: regulation and enforcement of the sale and distribution of substances. Conclusion: This study highlights adolescent substance use as a critical public health concern in Belize. The findings highlight the importance of moving beyond generalized prevention frameworks and adopting context-specific strategies that actively engage adolescents and address their developmental and psychosocial needs. Integrating efforts from various sectors through a multisectoral approach is crucial to effectively address substance use problems among adolescents.